2020
DOI: 10.1093/mnras/staa1395
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the magnetization of the cosmic web using LOFAR Faraday rotation observations

Abstract: Measuring the properties of extragalactic magnetic fields through the effect of Faraday rotation provides a means to understand the origin and evolution of cosmic magnetism. Here, we use data from the LOFAR Two-Metre Sky Survey (LoTSS) to calculate the Faraday rotation measure (RM) of close pairs of extragalactic radio sources. By considering the RM difference (ΔRM) between physical pairs (e.g. double-lobed radio galaxies) and non-physical pairs (i.e. close projected sources on the sky), we statistically isola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 92 publications
1
74
0
Order By: Relevance
“…The background map shows Hα intensity from WHAMSS (Haffner et al 2003(Haffner et al , 2010. the intrinsic FD of the EGSs (∼ 10-100 rad m −2 ; e.g., Schnitzeler 2010;Oppermann et al 2015;Anderson et al 2019), magnetic fields in the intergalactic medium ( 10 rad m −2 ; e.g., Vernstrom et al 2019;O'Sullivan et al 2020), and the uncertainty of our measurements (≈ 2 rad m −2 ). The use of SEM as our FD uncertainty implicitly assumes that the above sources of FD contaminations are not spatially correlated, which is not strictly the case for small-scale Galactic magnetic field (see Haverkorn et al 2008).…”
Section: Identification From Newly Derived Faraday Depthsmentioning
confidence: 76%
“…The background map shows Hα intensity from WHAMSS (Haffner et al 2003(Haffner et al , 2010. the intrinsic FD of the EGSs (∼ 10-100 rad m −2 ; e.g., Schnitzeler 2010;Oppermann et al 2015;Anderson et al 2019), magnetic fields in the intergalactic medium ( 10 rad m −2 ; e.g., Vernstrom et al 2019;O'Sullivan et al 2020), and the uncertainty of our measurements (≈ 2 rad m −2 ). The use of SEM as our FD uncertainty implicitly assumes that the above sources of FD contaminations are not spatially correlated, which is not strictly the case for small-scale Galactic magnetic field (see Haverkorn et al 2008).…”
Section: Identification From Newly Derived Faraday Depthsmentioning
confidence: 76%
“…These were the radio galaxies PMN J0351-2744 (e.g., Lenc et al 2017) We identify these four sources plus a further six physical pairs of polarised sources ('polarised doubles') in POGS ExGal, two examples of which are shown in Figure 5. Samples of such physical pairs of polarised sources can be used to provide constraints on the magnetised Cosmic Web (e.g., Vernstrom et al 2019;O'Sullivan et al 2020), but in order to derive meaningful constraints, we would require significantly higher surface density than is achieved with our MWA Phase I polarisation work.…”
Section: Notes On Individual Sourcesmentioning
confidence: 99%
“…Indeed, in recent years, the low-frequency polarised sky has been explored in greater detail than ever before, with detections of large-scale diffuse Galactic foreground along many lines of sight (LOSs) (e.g., Jelić et al 2015;Lenc et al 2016;Van Eck et al 2017 as well as many surveys that have begun to study the polarised extragalactic source population (e.g., Bernardi et al 2013;Mulcahy et al 2014;Van Eck et al 2017;Lenc et al 2018;Neld et al 2018;O'Sullivan et al 2019O'Sullivan et al , 2020Stuardi et al 2020;Cantwell et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These catalogs are also powerful tools for the study of extragalactic large-scale magnetic fields, as shown by Bonafede et al (2010), who determined the Coma cluster magnetic field strength from RMs. Moreover, due to the high sensitivity and high precision of new-generation radio interferometers, RM catalogs of polarized radio sources will be key components for the investigation of the magnetization of the cosmic web (e.g., Vacca et al 2016;O'Sullivan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Van Eck et al (2018) reported developments in polarization processing for the 570 deg 2 preliminary data release region from the LOFAR Two-Metre Sky Survey (LoTSS 2 , Shimwell et al 2017Shimwell et al , 2019 and presented a catalog of 92 polarized radio sources at 150 MHz with 4.3arcmin resolution and 1 mJy root mean square (rms) sensitivity. O'Sullivan et al (2019) presented the Faraday RM and depolarization properties of a giant radio galaxy using LOFAR and demonstrated the potential of LOFAR to probe the weak signature of the intergalactic magnetic field (see also O'Sullivan et al 2020).…”
Section: Introductionmentioning
confidence: 99%